From the History of the Infection Study - L. M. Farkhutdinova (Архивъ внутренней медицины)
The article reflects the development of ideas about infection, from the ancient period to the present day. In the V century Hippocrates proposed a miasmatic theory, according to which diseases are caused by harmful fumes. This paradigm remained dominant for 2.5 millennia. Although the existence of microorganisms has been known since 1676, when they were first described by Anthony van Leeuwenhoek, for a long time the detection of microbes in the biosubstrates of a sick person was considered as a secondary phenomenon in relation to the disease. The theoretical basis for such ideas was the concept of spontaneous generation, which has dominated since the time of Aristotle. The change from the miasmatic theory to the infectious paradigm was due to the fundamental discoveries of Louis Pasteur, who proved the biological nature of fermentation and the infectious genesis of silkworm diseases. The listed discoveries put an end to the discussion about spontaneous generation, became the scientific justification for asepsis and antiseptics and aimed at searching for pathogens of infectious human diseases, which led to a surge in discoveries in microbiology. The causative agents of fever (1868), leprosy (1873), anthrax (1876), tuberculosis (1882), cholera (1883), diphtheria (1884), plague (1894), etc. were discovered. As a result, the infectious theory finally conquered the world. An important achievement of the late 19th century was the allocation of a new type of infectious agents — viruses, which make up the most numerous form of life. With the recognition of the infectious theory at the end of the 19th century an active search for antimicrobial agents began. In 1943, the mass production of the first antibiotic, penicillin, was launched, the discovery of which is called one of the most outstanding achievements in the history of mankind. The use of antimicrobial drugs, along with mass vaccination, led to a significant decrease in the share of infectious diseases in the structure of mortality.